KRT81 and HNF1A expression in pancreatic ductal adenocarcinoma: investigation of predictive and prognostic value of immunohistochemistry‐based subtyping - Jia Rao; Marianne Sinn; Uwe Pelzer; Hanno Riess; Helmut Oettle; Ihsan E Demir; Helmut Friess; Carsten Jäger; Katja Steiger; Alexander Muckenhuber (Wiley, 2024)
Abstract Even after decades of research, pancreatic ductal adenocarcinoma (PDAC) remains a highly lethal disease and responses to conventional treatments remain mostly poor. Subclassification of PDAC into distinct biological subtypes has been proposed by various groups to further improve patient outcome and reduce unnecessary side effects. Recently, an immunohistochemistry (IHC)‐based subtyping method using cytokeratin‐81 (KRT81) and hepatocyte nuclear factor 1A (HNF1A) could recapitulate some of the previously established molecular subtyping methods, while providing significant prognostic and, to a limited degree, also predictive information. We refined the KRT81/HNF1A subtyping method to classify PDAC into three distinct biological subtypes. The prognostic value of the IHC‐based method was investigated in two primary resected cohorts, which include 269 and 286 patients, respectively. In the second cohort, we also assessed the predictive effect for response to erlotinib + gemcitabine. In both PDAC cohorts, the new HNF1A‐positive subtype was associated with the best survival, the KRT81‐positive subtype with the worst, and the double‐negative with an intermediate survival (p < 0.001 and p < 0.001, respectively) in univariate and multivariate analyses. In the second cohort (CONKO‐005), the IHC‐based subtype was additionally found to have a potential predictive value for the erlotinib‐based treatment effect. The revised IHC‐based subtyping using KRT81 and HNF1A has prognostic significance for PDAC patients and may be of value in predicting treatment response to specific therapeutic agents.